2021
DOI: 10.1161/strokeaha.120.031971
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke, Inflammation, and Endotheliopathy in COVID-19 Patients

Abstract: Background and Purpose: Reports indicate an increased risk of ischemic stroke during coronavirus disease 2019 (COVID-19) infection. We aimed to identify patients with COVID-19 and ischemic stroke and explore markers of inflammation, hypercoagulability, and endotheliopathy, a structural and functional disturbance of the vascular endothelium due to a stressor. Methods: This was a retrospective, observational cohort study comparing acute ischemic stroke pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…From clinical observations, it was noted elevated concentration of D-D dimer, fibrinogen, and CRP in COVID-19 patients with acute ischemic stroke, suggesting systemic hyperinflammatory and hypercoagulable state (34). In a retrospective, observational cohort study, CRP was found to be correlated between stroke onset and the peak of acute phase reactants in COVID-19 (35). Furthermore, CRP was the mortality predictor, and its expression might be correlated with the formation of ischemia in COVID-19 associated strokes (36).…”
Section: Crp and Stroke In Covid-19mentioning
confidence: 99%
“…From clinical observations, it was noted elevated concentration of D-D dimer, fibrinogen, and CRP in COVID-19 patients with acute ischemic stroke, suggesting systemic hyperinflammatory and hypercoagulable state (34). In a retrospective, observational cohort study, CRP was found to be correlated between stroke onset and the peak of acute phase reactants in COVID-19 (35). Furthermore, CRP was the mortality predictor, and its expression might be correlated with the formation of ischemia in COVID-19 associated strokes (36).…”
Section: Crp and Stroke In Covid-19mentioning
confidence: 99%
“…The average age of non-COVID-19 patients with ischemic stroke is around 74 years old; however, multiple cohorts worldwide have found that the average age of patients with COVID-19 and concurrent ischemic stroke is substantially younger, ranging between 54.9 and 64 years old (7,(36)(37)(38)(39). It is unclear why COVID-19 increases stroke risk in younger individuals out of proportion to what would be expected in non-COVID-19 cohorts, but we hypothesize that younger patients may be more susceptible to endothelial injury as we note in our previously published study from either the direct infection or an post-infectious immunologic pathway that needs to be further elucidated (5). There may also be selection bias at play, as older patients with COVID-19 may be more likely to withdraw care and less likely to undergo further stroke testing.…”
Section: Discussionmentioning
confidence: 79%
“…As of March 2021, the global pandemic caused by coronavirus disease 2019 (COVID- 19) has infected more than 120 million individuals worldwide and has resulted in more than 2.6 million deaths (1). Although COVID-19 commonly manifests as a respiratory illness, it is also linked with an increased risk of cerebrovascular disease by multiple potential pathophysiologic mechanisms, including inflammation, hypercoagulability, and endotheliopathy (2)(3)(4)(5). Among patients with COVID-19 in a cohort in Wuhan, China, those with a history of ischemic stroke had more co-morbidities, lower platelet and leukocyte counts, and higher D-dimer, pro-brain natriuretic peptide, and interleukin-6 levels compared to their counterparts without a prior history of stroke (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher levels of IL-6 and sIL-2R were noted in COVID-19 patients. This evidence suggests endotheliopathy and systemic inflammation are more frequent in COVID-19 patients leading to ischemic stroke in patients with vascular risk factors compared to control groups [ 74 ].…”
Section: Introductionmentioning
confidence: 99%